Design and Implementation of Web-Based Online New Student Admission Information System (PPDB) at As-Syifa Kindergarten/PAUD - Muhammad Fachri; Muhamad Rizqi; Bisma Alifia; Afiani Agus Abdillah (Takaza Innovatix Labs Ltd., 2026)
TK/PAUD As-Syifa in Pondok Aren, South Tangerang, still runs its student admission process (PPDB) manually: parents come to school, fill in paper forms, and wait for confirmation. The process is slow, prone to data loss, and places a heavy administrative burden on staff. This study built a web-based PPDB information system to replace that process. The system was developed using CodeIgniter, PHP, MySQL, and Bootstrap, following a Waterfall development approach with UML modeling. Testing used Black Box Testing across 56 test scenarios in eight functional categories, covering multi-step registration forms, user authentication, verification, and session security. Every scenario passed without exception, yielding a 100% success rate. As a result, parents can register independently at any time, administrators can verify data and download Excel reports on demand, and the risk of data loss is substantially reduced.